Dynamic equilibrium and volatility in financial asset markets - Aït-Sahalia, Yacine (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1996)
This paper develops and estimates a continuous-time model of a financial market where investors' trading strategies and the specialist's rule of price adjustments are the best response to each other. We examine how far modeling market microstructure in a purely rational framework can go in explaining alleged asset pricing ànomalies.' The model produces some major findings of the empirical literature: excess volatility of the market price compared to the asset's fundamental value, serially correlated volatility, contemporaneous volume-volatility correlation, and excess kurtosis of price changes. We implement a nonlinear filter to estimate the unobservable fundamental value, and avoid the discretization bias by computing the exact conditional moments of the price and volume processes over time intervals of any length.